О чем плачут лошади: рассказы / Федор Абрамов - Абрамов Федор Александрович (Школьная библиотека)
Экземпляры: аб. (2012) / Инвентарный номер: 54091 / Цена: 183.02 / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 16 / ГРНТИ: 17.82.32 / ББК: 84(2Рос=Рус)6-44